KAJIAN POTENSI AKTIVITAS ANTIOKSIDAN DAN SENYAWA FENOLIK EKSTRAK RUMPUT LAUT Gracilaria verrucosa DARI PANTAI SUNDAK, KABUPATEN GUNUNG KIDUL - Heraedi, Arifin; Dewi, Eko Nurcahya; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Gracilaria verrucosa seaweed from southern coastal waters, thought to have antioxidant bioactive compounds such as phenolic compounds, pigments and vitamins. The purpose of this study was to determine whether there is any potential antioxidant activity of extracts of seaweed Gracilaria verrucosa and find compounds that contribute to antioxidant activity. This research is an experimental research laboratories using Randomized Block Design (RBD) with treatment of three different types of solvent polarity level of the n-hexane, ethyl acetate, and ethanol. Parameters measured were qualitative test antioxidants, phytochemical screening, antioxidant activity performed by DPPH method, the measurement of total phenolic content, the levels of chlorophyll and carotenoids. The result showed the highest antioxidant activity present in the ethyl acetate extract with IC50 value of 278.082 ppm. Phytochemical screening test results known alkaloid compounds, phenolic steroid found in all kinds of Gracilaria verrucosa extracts. The highest total phenolic contained in the ethyl acetate extract of 51.09 mg GAE / g extract, levels of chlorophyll a, chlorophyll b and carotenoids highest in ethyl acetate extract is 2.6 mg / g sample; 2.211 mg / g sample, and 1.594 mg / g sample. Gracilaria verrucosa generated are semi-polar, and the dominant compounds of antioxidants are phenolic compounds, chlorophyll b and carotenoids